2012
DOI: 10.1103/physreve.85.041123
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature behavior of a deformed Fermi gas obeying interpolating statistics

Abstract: An outstanding idea originally introduced by Greenberg is to investigate whether there is equivalence between intermediate statistics, which may be different from anyonic statistics, and q-deformed particle algebra. Also, a model to be studied for addressing such an idea could possibly provide us some new consequences about the interactions of particles as well as their internal structures. Motivated mainly by this idea, in this work, we consider a q-deformed Fermi gas model whose statistical properties enable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 89 publications
0
43
0
Order By: Relevance
“…However, it is easy to see that, although both of these formulations are equivalent for a( f ) = f , for another choice of a( f ) different from the identity, Equations (16) and (17) in general do not coincide.…”
Section: Generalized Exclusion-inclusion Principlementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is easy to see that, although both of these formulations are equivalent for a( f ) = f , for another choice of a( f ) different from the identity, Equations (16) and (17) in general do not coincide.…”
Section: Generalized Exclusion-inclusion Principlementioning
confidence: 99%
“…Therefore, the study of physical systems that obey non-conventional statistics is one of the pillars of contemporary statistical physics [6][7][8][9][10][11][12]. Their interest spans from the theoretical foundation of generalized statistical mechanics [13,14], Fermi gas superfluid [15], high-temperature gas [16] and high-T c superconductivity [17], Laughlin particle with fractional charge related to fractional quantum Hall effect [18,19], Josephson junctions [20] and applications to quantum computation [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we will carry it out a Taylor expansion until second order of Eq. (25), which allows us the analysis of the insertion of the q-deformation. After performing some calculations we obtain…”
Section: A Q-fermions Applicationmentioning
confidence: 99%
“…The -deformed scalar field is in fact a -deformed boson model, and the statistical mechanical studies ofdeformed boson models have shown that the pressure of the deformed bosons is generally negative. Not only do the 2 Advances in High Energy Physics different deformed boson models have a negative pressure, but also the different deformed fermion models can take negative pressure values [46][47][48][49][50]. Here, we consider thedeformed bosons and propose that the scalar field which is produced by these deformed bosons constitutes the dark energy in the universe.…”
Section: Introductionmentioning
confidence: 99%